Risk Factor Analysis and PM2.5 Concentration on Community Lung Capacities Around the Konawe Industrial Area - Asterina, Devi Cessaria; Jayadipraja, Erwin Azizi; Nirwan, Muhammad (Magister Kesehatan Universitas Mandala Waluya, 2023)
Backgrounds: Communities residing in industrial areas are the group most at risk of PM10 exposure. The Nickel Processing Industrial Area in Konawe Regency, Southeast Sulawesi Province is one of the largest in Indonesia. Communities living in the Industrial Area include Morosi District, Motui District, and Kapoiala District. Methods: The type of research used is quantitative research with a cross-sectional study design. The target population in this study is 2,420 people divided into 6 villages. The research sample was 343 people. Data analysis used the chi-square test. Results: The results of the analysis of the relationship to lung capacity obtained a history of respiratory disease with a p-value (0.000) < 0.05, the presence of smokers at home with a p-value (0.003) < 0.05, physical activity with a p-value (0.008) < 0.05, and PM2.5 concentration with p-value (0.397) > 0.05. Conclusion: There is a relationship between the history of disease, the presence of smokers in the house, and physical activity with the lung capacity of the community and there is no relationship between PM2.5 concentration with community lung capacity around the Konawe Industrial Area.